MORPHOMETRY OF THE GILL AND ARBORESCENT STRUCTURES OF Clarias gariepinus (BURCHELL, 1822) AT DIFFERENT DEVELOPMENTAL STAGES - Nuriliani, Ardaning; Karlina, Ina; Rohmah, Zuliyati; Sari, Dini Wahyu Kartika (Politeknik Kelautan dan Perikanan Karawang, BRSDM KP., 2025)
Catfish is one of Indonesia's superior fishery commodities. Catfish have an adaptation mechanism to an environment with minimal oxygen in their gill structure, namely arborescent to support their successful lives. This study examines Mutiara catfish's gill and arborescent morphometry at various developmental stages. The morphometric parameters consist of several parts, namely gill structure and arborescent structure. The gill structure includes the ratio of gill weight right and left to the weight and total length of the fish. Apart from that, the gills are divided into three main parts, namely the branchial arch, branchial filaments, and branchiospinalis. The part of the branchial arch observed includes the ratio of the length of the branchial arch to the total length of the fish. The branchial filament section includes the average number of branchial filaments per branchial arch, the average density of branchial filaments (filaments/cm), and the ratio of branchial filament length to branchial arch length. The branchiospinal section includes the average number of branchiospinalis per branchial arch and branchiospinal density. Arborescent structures include ratios of relative arborescent weight (%) right and left to total fish weight and the ratio of the number of arborescent branches to total arborescent weight. Catfish were sampled from the larval stage (1–14 days), juvenile (15–21 days), and post-juvenile to pre-adult (22–90 days). Statistical analysis of data using SPPS 22 software. Mutiara catfish in the post-adolescent to preadult stage have higher relative gill weight and relative arborescent weight than the juvenile and larval stages. The post-adolescent to preadult stage has a more developed gill and arborescent shape and size than the juvenile and larval stages.